Residue retention and precision nitrogen management effects on soil physicochemical properties and productivity of maize-wheat-mungbean system in Indo-Gangetic Plains - Dinesh, Govindaraj Kamalam; Sharma, Dinesh Kumar; Jat, Shankar Lal; Venkatramanan, Veluswamy; Boomiraj, Kovilpillai; Kadam, Praveen; Prasad, Shiv; Anokhe, Archana; Selvakumar, Selvaraj; Rathika, S.; Ramesh, T.; Bandyopadhyay, Kalikinkar; et al. (Frontiers in Sustainable Food Systems, 2024)
Maize-based crop systems are promoted in large scale in South Asia because they are more sustainable and efficient than rice-based systems. In the present study, using two combinations of crop residue management practices (CRM) with four precision nitrogen (N) management (PNM) systems, we assessed the impacts on soil physicochemical characteristics [soil organic carbon (SOC), bulk density (BD), soil penetration resistance (PR)] and crop yields in 6 years old continuous zero tillage (ZT) practices under maize-wheat-mungbean cropping system in a sandy loam soil of northwestern India. The highest SOC (5.73 g/kg) was observed in Zero Tillage with Residue Retention (ZT + R) plots. Zero-tillage with residue retention (ZT + R) significantly reduced the bulk density over the zero-tillage with no residue retention (ZT-R) across the soil depth. The bulk density in ZT + R was 6.5 and 10.7% lower at 0–15 cm and 15–30 cm soil depth, respectively, than under ZT-R. The penetration resistance (PR) was significantly lower in ZT + R than in ZT-R across the soil depth. Soil organic carbon (SOC) in ZT + R was 7.4% higher at 0–15 cm depth and 11.9% higher at 15–30 cm depth than under ZT-R treatment. Among PNM treatments, the sequence of treatments in SOC content was 50%N + Green Seeker (GS) >33%N + GS > RDN > 70%N + GS. The system productivity (maize equivalent yield) under ZT + R in combination with 50%BN + GS was 15.0% higher than crops grown under ZT-R with RDN. The wheat equivalent yield under the ZT + R treatment is found to be higher (5.97) in the 50%BN + GS, which was 18% higher than the recommended dose of nitrogen treatment (5.04) and 28% higher than the 70%BN + GS treatment (4.68). Results demonstrated that plots with residue retention performed better, showing a 10% increase in system productivity. The study concludes that a ZT-based system with maize-based crop rotations (MWMb) with crop residue retention and precision nitrogen management can improve soil properties and system productivity in northwestern India.